Front Office Management / In Hospitality Lodging Operations - Casado Matt A (2014)
This book offers comprehensive coverage of topics related to front office operations, including a review of technologies current in use, and an array of situations students are bound to find on the job. Preface, Introduction to Front Office Management, The Front Office Manager in Hospitality Lodging Operations, The Front Office Manager in Lodging Operations, Management Concepts as they Apply to the Front Office Manager, The Front Office Manager as Department Head, Other Management Responsibilities of the Front Office Manager, Design of the Front Office in Lodging Operations, Front Office Technology, Synopsis of Front Office Automation, Professional Aspects of Front Office Management, Effective Communication at the Front Office, Rooms Rates and Reservations, Front Office Operations, Front Office Financial Controls and Security and Job-Seeking Strategies, Glossary, Index.